In vitro regeneration of castor (Ricinus communis L.): In vitro regeneration of castor (Ricinus communis L.) - B USHA KIRAN,; V DINESH KUMAR,; H H KUMARASWAMY,; M SUJATHA, (Journal of Oilseeds Research, 2020)
Standardization of a reliable regeneration protocol is important in castor to develop transgenics conferring resistance to biotic and abiotic stresses. An attempt has been made to developan in vitro regeneration protocol using the hypocotyl explants derived from seedlings obtained from decoated seeds. Out of 60 different hormonal combinations tried, three combinations showed better shoot induction and the rooting was better with IBA 1.0 mg/L.